Targeted Therapy for Low Back Pain in Elderly Degenerative Lumbar Scoliosis: A Cohort Study. Issue 10 (May 2016) - Yamada, Kiyotaka; Nakamae, Toshio; Shimbo, Takuro; Kanazawa, Toshikatsu; Okuda, Teruaki; Takata, Haruhiko; Hashimoto, Takashi; Hiramatsu, Takeshi; Tanaka, Nobuhiro; Olmarker, Kjell; Fujimoto, Yoshinori
Abstract : Study Design: Prospective cohort study. Objective: To compare the novel treatment procedure with nonoperative treatment for low back pain (LBP) in elderly patients with degenerative lumbar scoliosis (DLS). Summary of Background Data: Treatment of LBP associated with elderly DLS is controversial. We developed a novel treatment procedure, termed percutaneous intervertebral-vacuum polymethylmethacrylate injection (PIPI). Methods: We included patients with de novo DLS aged ≥65 years who had LBP with a visual analogue scale (VAS) score of >50 for ≥6 months with intervertebral vacuum and vertebral bone marrow edema (BME) defined on fat-saturated T2-weighted or gadolinium-enhanced T1-weighted magnetic resonance imaging. The primary outcomes were evaluated using the VAS score and modified Oswestry Disability Index (ODI). As an objective measurement, we scored BME on magnetic resonance imaging. Results: Between August 2004 and July 2011, 109 patients underwent PIPI and 53 received nonoperative treatment. At 1 month, mean improvements in VAS scores were −55.3 (95% CI, −60.5 to −50.1) and −1.9 (CI, −7.7 to 3.8) and mean improvements in ODI were −22.7 (CI, −27.3 to −18.2) and −0.6 (CI, −6.6 to 5.4) for the PIPI and nonoperative groups, respectively. At 2 years, mean improvements in VAS scores were −52.2 (CI, −59.9 to −44.4) and −4.0 (CI, −10.9 to 3.0) and mean improvements in ODI were −20.7 (CI, −27.3 to −14.5) and −1.0 (CI, −7.7 to 5.7) for the PIPI and nonoperative groups, respectively. BME substantially decreased in the PIPI group compared with the nonoperative group ( P  <0.001) and correlated with VAS score and ODI improvements (VAS score: r  = 0.502, P  <0.001; ODI: r  = 0.372, P  <0.001). Conclusion: PIPI improved treatment for LBP, with a sustained clinical benefit for at least 2 years. Level of Evidence: 3